Introduction to linear regression analysis - Montgomery, Douglas C.; Peck, Elizabeth A., 1953-; Vining, G. Geoffrey, 1954- (Hoboken, NJ : Wiley, 2012)
"This book describes both the conventional and less common uses of linear regression in the practical context of today's mathematical and scientific research"--
Περιέχει βιβλιογραφία και ευρετήριο.
Keywords: Regression analysis; Mathematics